Point-of-Care Assessment of Direct Oral Anticoagulation in Acute Ischemic Stroke: Protocol for a Prospective Observational Diagnostic Accuracy Study - Sedghi, Annahita; Heubner, Lars; Klimova, Anna; Tiebel, Oliver; Pietsch, Jörg; Mirus, Martin; Barlinn, Kristian; Minx, Tabea; Beyer-Westendorf, Jan; Puetz, Volker; Spieth, Peter; Siepmann, Timo (Thrombosis and Haemostasis, 2022)
Background Treatment of ischemic stroke with recombinant tissue plasminogen activator for intravenous thrombolysis (IVT) must be delivered within a narrow time window after symptom onset. This effective hyperacute treatment can be administered after ruling out active anticoagulation with direct oral anticoagulants (DOACs). Whenever this is impractical, e.g., due to aphasia, plasmatic DOAC levels are measured with a consequent delay in the IVT decision-making process ranging from 30 to 60 minutes of time. This study will test the hypothesis that hyperacute point-of-care assessment of clotting time in the patient's whole blood has sufficient diagnostic accuracy to determine immediately whether stroke patients are pretreated with DOAC.Methods and Design This will be a prospective single-center diagnostic accuracy study in 1,850 consecutive acute ischemic stroke patients at a tertiary stroke center in Saxony, Germany. Presence of active anticoagulation with DOAC will be determined by point-of-care quantification of clotting time via whole blood viscoelastic testing (ClotPro) using Russell venom viper and ecarin assay compared with high-performance liquid chromatography-tandem mass spectrometry as the reference standard.Discussion Viscoelastic point-of-care assessment of clotting time in whole blood might improve swift delivery of time-sensitive hyperacute treatment with IVT in stroke patients.
Keywords: stroke prevention; thrombolysis; oral anticoagulants; inhibitors